A Review on Emotional Recognition System Based E-learning: Technology and Challenges - Fadahl Alhaboobi Z.A.; Singh Sidhu M.; Hilaluddin T. (Institute of Electrical and Electronics Engineers Inc., 2023)
Brain; Deep learning; E-learning; Learning systems; Body activities; Electronic learning (e-learning); Emotional recognition; Learning management system; Multiple technology; State-of-the-art technology; Engineering education